2004
DOI: 10.1590/s0041-87812004000300010
|View full text |Cite
|
Sign up to set email alerts
|

Proton magnetic resonance spectroscopy of the frontal lobe in schizophrenics: a critical review of the methodology

Abstract: Schizophrenic patients undergoing proton magnetic resonance spectroscopy show alterations in N-acetyl aspartate levels in several brain regions, indicating neuronal dysfunction. The present review focuses on the main proton magnetic resonance spectroscopy studies in the frontal lobe of schizophrenics. A MEDLINE search, from 1991 to March 2004, was carried out using the key-words spectroscopy and schizophrenia and proton and frontal. In addition, articles cited in the reference list of the studies obtained thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 44 publications
2
8
0
Order By: Relevance
“…20 In particular, most (8 of 15) published studies of the hippocampus report a significant reduction of NAA in patients. The present findings therefore add to evidence of NAA abnormalities in schizophrenia, [16][17][18][19][20] in subjects at risk for schizophrenia, [27][28][29]31 and extend them to the particular case of twin siblings. But the direction of our NAA findings (excess vs deficit) is at odds with the abovecited literature.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…20 In particular, most (8 of 15) published studies of the hippocampus report a significant reduction of NAA in patients. The present findings therefore add to evidence of NAA abnormalities in schizophrenia, [16][17][18][19][20] in subjects at risk for schizophrenia, [27][28][29]31 and extend them to the particular case of twin siblings. But the direction of our NAA findings (excess vs deficit) is at odds with the abovecited literature.…”
Section: Discussionsupporting
confidence: 78%
“…Reviews of the MRS schizophrenia literature to date [16][17][18][19][20] show ample evidence of abnormalities in NAA; suggestive evidence for abnormalities in glutamate þ glutamine (Glx), Cr and choline (Cho); and scant evidence for abnormalities in mI. In particular, bilateral deficits in NAA, NAA/Cr and/or NAA/Cho in the 'dorsolateral prefrontal' region (usually middle frontal gyrus) and mesial temporal lobes (predominantly hippocampus) were detected in early work in adult schizophrenia 21 and have since become fairly accepted.…”
Section: Introductionmentioning
confidence: 99%
“…The spatial resolution in 1 H‐MRS remains a problem, especially in studies using larger voxel (Sanches et al . ). Furthermore, control participants and patient groups assessed serially often differ in the exact amount of each tissue in the specified voxel and the localization of the VOI lacks sufficient accuracy to assure a direct comparison (Marshall et al .…”
Section: Discussionmentioning
confidence: 97%
“…However, many studies found decreased NAA levels as in CSP (Sanches et al . ; Jessen et al . ), in early and late at‐risk syndrome patients that converted to schizophrenia (Jessen et al .…”
Section: H‐mrs Findings In Schizophreniamentioning
confidence: 99%
“…Relative ratios may be calculated by dividing NAA concentrations by the concentration of a metabolite whose concentration would be expected to be stable, such as creatine (Cr) or choline (Cho). However, a reduction of NAA in the frontal and cingulate areas of patients with schizophrenia has not been found consistently (16)(17)(18). These contradictory findings may be due, in part, to the heterogeneous characteristics of schizophrenia, or to different methodological approaches.…”
Section: Introductionmentioning
confidence: 97%